Evaluación de la actividad coagulante, hemostática y toxicidad aguda por vía oral y tópica del extracto seco hidroalcohólico al 70% de Castilleja pumila - Mendoza, Shirley (2019)
ABSTRACT The present work has the objective of demonstrating the coagulant, hemostatic activity and acute toxicity via oral and topical of the 70% hydroalcoholic dry extract of Castilleja pumila (misk’icha), in venous blood samples and in wounds produced in mice; The method used was a qualitative phytochemical analysis and a solubility study of the hydroalcoholic extract at 70%. A quasi-experimental study was conducted with only post-test and control group; furthermore, the experimental animals were not randomly assigned; rather, these groups were already formed before the experiment. A reduction percentage of the clotting time of 15.67% was obtained for dose 3 (C3 = 1mg / mL), so it can be concluded that this dose is the most effective; and a percentage decrease in prothrombin time of 44%, for dose 3 (C3 = 1mg / mL), so it can be concluded that this dose is the most effective. For hemostatics, a percentage of the hemostasis decrease time of 10.34% was obtained, with dose 3 (C3 = 1000mg / kg) from which we conclude that this is the most effective dose. According to the proposed methodology, the animals were observed, and during this time there was no significant presence, that is, representative morphological changes, thus determining that under this test a topical toxicity occurs in a minimum degree, from zero to four. There was also no significant presence in terms of signs and symptoms in the animals, nor did any of them die, therefore, it was determined that at the doses evaluated the extract does not present acute oral toxicity. In conclusion, the present study provides scientific evidence of Castilleja pumila for the treatment of bleeding, it presents mild to moderate oral and dermal toxicity.